Identification of mechanisms that drive water level extremes from in situ measurements in the Gulf of Riga during 1961–2017. (1st July 2019) - Männikus, Rain; Soomere, Tarmo; Kudryavtseva, Nadezhda
Abstract: We analyse a two-step mechanism for the formation of extremely high water levels in a semi-enclosed sub-basin of the Baltic Sea with the pumping of large amounts of water first into this sea and then into the Gulf of Riga. The analysis is based on hourly water level recordings at two observations sites in the gulf (Pärnu and Daugavgriva) and at one station (Liepaja) on the eastern shore of the Baltic Sea proper in the period 1961–2017. The empirical distributions of the probability of occurrence of different water levels have a classic quasi-Gaussian shape but are asymmetric: elevated water levels are more likely than negative surges. The highest recorded water levels in the interior of the Gulf of Riga exceed those on the open eastern coasts of the Baltic Sea proper by more than 1 m once in 5–10 years. The time scale of generation and relaxation of such elevated levels is about one day. There is no increase in the magnitude of episodes of strongly elevated water levels in the Gulf of Riga since the 1960s. The annual average number of episodes of significant differences between the water level at Liepaja and Pärnu has decreased by a factor of 1.6 whereas differences between Liepaja and Daugavgriva did not change. This pattern of changes indicates an alteration of the directional structure of winds in this area. Highlights: Storms may bring large volumes of excess water into the Gulf of Riga. Water level in the gulf may exceed the Baltic Sea level by 1 m once in 5–10 years. The recorded water level extremes in the gulf reflect such events. The magnitudes of such events shows no changes since the 1960s. The pattern of changes indicates an alteration of the directional structure of winds.